Determining the Role of Ki67 and p16INK4a Biomarkers on Conventional Cell Blocks to Differentiate Post Radiation Dysplasia from Cervical Cancer in Post Therapeutic Surveillance Cytology - F. S. Desai; Rajesh Korant; Mehul Gohil; Lisam Shanjukumar Singh (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Introduction: Although pap test is effective to screen abnormal cervical cytology before therapy, it is not very useful after therapy because of radiation-induced changes. Diagnostic accuracy of post therapy Papanicolaou (pap) tests is low, as it is difficult to differentiate benign from malignant lesions due to post radiation cellular changes, also known as post radiation dysplasia. Aims and Objectives: In this study we have evaluated the role of biomarker p16INK4a and Ki67on conventional cell blocks (CCBs) in post therapeutic surveillance of cervical cancer to detect residual disease and site recurrence. We have also evaluated CCBs as a primary screening test. Materials and Methods: In this cross-sectional study, patients who were diagnosed as cervical cancer before one year were followed between periods of April 2018-April 2019. We collected conventional pap smears and samples in 10% neutral buffered formalin for CCBs. The immunohistochemistry was performed on all cell blocks using Ki67 and p16INK4a as primary antibodies. Results: Out of total 35 cases, recurrences and residual disease were diagnosed in 8 cases. Sensitivity, specificity, diagnostic accuracy for pap, cell blocks and p16INK4a for detecting cervical cancer were 75%, 74.07%, 88.57%; 100%, 88.89%, 91.43% and 37.50%, 96.30% and 82.86% respectively. We observed that Ki67 labeling index \(≥\) 20% had a diagnostic accuracy of 100%. Conclusion: Our findings suggest that Ki67 labeling index \(≥\)20% on CCBs can differentiate residual and recurrent cancer from post radiation dysplasia in post therapy surveillance cytology (p value <0.001). We also observed that CCBs has better diagnostic accuracy than pap test (Mac Nemar p value, 0.027). We did not found p16INK4A much useful as a biomarker in evaluation recurrence/residual disease.